A Comprehensive Assessment of the Quality of Supplied Drinking Water in Galyang Municipality of Syangja, Nepal - Bhandari, Hari; Sapkota, Kamal Prasad (Amrit Journal, 2023)
A thorough assessment on the municipally supplied water samples from Malunga and Galyang cities; two different places in the Syangja district focused on analyzing various water quality parameters. These parameters included pH value, alkalinity, electrical conductivity, turbidity/suspended solids, chloride contents, and the presence of acid and basic radicals (heavy metal ions). The results obtained from standard laboratory probes carried out on-site and at the chemistry laboratory of Amrit Campus, indicated that the pH value, alkalinity, electrical conductivity, chloride contents, and the presence of acid radicals (nitrate, sulfate, and chloride) and basic radicals (toxic heavy metal ions) in the water samples were all within the safe limits for potable water as suggested by both the National Drinking Water Quality Standards (NDWQS) of Nepal and the World Health Organization (WHO). However, it was disclosed that the total suspended solids in the water samples existed in higher concentrations, leading to coagulation and the formation of thin, flat, whitish lumps during long-term storage of the samples. Overall, while the study determined that the water samples concurred the safe limits for most parameters set by NDWQS and WHO, the higher concentration of total suspended solids during prolonged storage suggests a potential attention to be paid for the improvement of the quality.